The Role of Women in the Domestic and Public Realms Gender Fiqh Perspectives - Marwah, Andi; Syatar, Abd; Bakry, Muammar (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This paper examines the role of women in the domestic and public sphere, aiming to provide an explanation related to matters related to the role of women in the domestic and public sphere. The methodology used in this study is a literature study using a gender fiqh approach, this paper explores how Islamic law can adapt to social changes, without ignoring the principles of sharia sourced from several relevant references to the topic discussed. Data collection techniques come from researching relevant reference sources in the form of journals, articles, websites, books and other scientific works. The analysis technique of this research is through collection, analysis and drawing conclusions. The results of this paper are about the role of women in the domestic sphere and describe the role of women in the public sphere which shows that the dual role of women can be achieved with a more inclusive and equitable approach to women, allowing them to play an active role in various areas of life without facing the double burden and obstacles of patriarchal structures.